Peran Pengelolaan Lingkungan Industri dalam Mengurangi Risiko Keselamatan Akibat Paparan Zat Kimia pada Fatty Alcohol Plant di PT Bakrie Renewable Chemicals - Rizki Fadhilah; Khairul Anshar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The oleochemical industry carries high occupational safety and health (K3) risks due to its use of chemicals, high pressure and temperature, and complex production processes, one example being the Fatty Alcohol Plant at PT Bakrie Renewable Chemicals. This study identifies potential hazards, assesses risk levels, and analyzes control measures for chemical exposure using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method, applying a descriptive-qualitative approach through field observation, interviews, document review, and literature study. Seven risk-prone activities were identified: chemical receiving, storage, raw material transfer, vapor leakage and ventilation, heating-cooling operations, distillation-purification, and maintenance, with two activities falling into the high-risk category, four into medium, and one into low. The highest risks were found in chemical vapor leakage (R=15) and process heating (R=12). Risk control follows the hierarchy of control: engineering controls, administrative controls, periodic inspection, ventilation improvement, gas detectors, preventive maintenance, and personal protective equipment (PPE), measures that reduce workplace accident risk while improving industrial environmental management.